Pembuatan Alat Peraga Sederhana untuk Mendukung Pembelajaran Fisika - Godelfridus Hadung Lamanepa; Petrus Ola Begu; Rosenti Pasaribu (Jurnal Pengabdian Masyarakat (abdira), 2022)
The problem of learning physics at the Oepoi Kupang Seminary High School is the limited use of teaching aids in physics learning. The purpose of the service activities carried out is to describe the satisfaction and benefits of the process of making teaching aids and the results of their use. Methods of implementation activities include observation and interviews, reviewing laboratory equipment, followed by preparation and training activities. The props made are binoculars, a hose and a U-pipe holder, and an image model for visualizing the formation of an object's image between two plane mirrors. The activity was carried out for three days and was attended by 25 students of class X SMA Seminar Oepoi Kupang. Furthermore, observations and filling out questionnaires on the satisfaction and benefits of participating in the activities carried out were carried out. The results of the activities carried out, the teacher and resource persons can make physics teaching aids that can explain physics material in more detail. The benefits and satisfaction of students participating in mentoring activities is that more than 80% of students are satisfied to feel the benefits of this mentoring activity.